Implementasi Kurikulum Dalam Peningkatan Mutu Lulusan Di Pesantren Modern Ainul Yaqin Padang Kudo Nagari Batagak Kec. Sungai Pua, Kab. Agam - Naswir N; Zulfani Sesmiarni (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the implementation of the curriculum in improving the quality of educational institutions, especially in the Ainul Yaqin Modern Islamic Boarding School. The main focus of this study is to determine how curriculum planning, implementation, and evaluation can have an impact on improving the quality of education in the institution. The type of research used is qualitative research with a case study approach, where data is collected through in-depth interviews with Islamic boarding school managers and teachers, direct observation, and analysis of the applied curriculum documents. The results of the study indicate that the implementation of a well-structured curriculum, based on the needs of students, and involves innovative teaching and ongoing evaluation. Adjusting the curriculum to the development of the times and the needs of society is also an important factor in this success. The conclusion of this study is that the implementation of an effective curriculum and in accordance with the objectives of the institution greatly influences the improvement of the quality of education, both in terms of religious knowledge and life skills, which in turn will improve the quality of the institution as a whole.